Comfort analysis in commercial vehicle's passenger seat - Tam, Wee Kong (2006)
A passenger seat is one of the main components to be considered when defining comfort in a moving vehicle. Experience shows that a seat produces different levels of comfort in different conditions. The comfort of automotive seats is dictated by a combination of static and dynamic factors. This research attempts to study the static and dynamic characteristics of a bus passenger seat for comfort through subjective and objective evaluations. The discomfort factors to be studied are the seat structure and pressure distribution at the human-seat interface. Two surveys including a pilot test were carried out to study the subjective evaluation through direct response from local users on seat comfort during their journey on the road. For the objective evaluation, two tests were conducted; SEAT (Seat Effective Amplitude Transmissibility) test and pressure distribution test. An SAE Sit-pad Accelerometer was used to measure vibration on the seat. Whereas, the pressure distribution at the human-seat interface was measured using pressure mapping system. Both tests had been carried out under controlled and uncontrolled conditions. Experimental works in the laboratory were considered as controllable. Uncontrolled condition refers to the road trials or field tests carried out in a moving vehicle which produced random vibrations. The results showed that, besides the postures and size of the passenger, the road conditions also have effects on the pressure distribution and SEAT data. A proposed seat structure with spring and damper properties was used and proved to be more effective in achieving seat vibration comfort. The SEAT values of this proposed seat were lower than the values for the current existing seat. A lower SEAT value means better ride comfort. By improving the seat parameters using the said method, vehicle seats, such as bus seats, could be developed with better ride comfort for local purposes.